Analisis Postur Kerja Dengan Metode Manual Task Risk Assessment (ManTRA) Pada Pembuatan Mie Sohun - Pratiwi, Indah; Miftahurrohman, Miftahurrohman; Djunaidi, Much.; Suranto, Suranto (Jurnal Ilmiah Teknik Industri, 2018)
One of the noodle sohun industry is located in Daleman Village, Klaten District. The process of making is done manually and using a simple tool, through 4 workstations, namely: palm sugar mill work station, palm juice cooking station, cooking station, and printing station. The purpose of the research is to find out the complaints of workers using Nordic Body Map (NBM) , the risk of work posture using the Manual Task Risk Assessment (ManTRA) method, and provide a safe solution to implement. The results of the NBM questionnaire showed that the categories with the very right shoulder pain were 36.4% and the left wrist was 36.4%. The results of the ManTRA method are: the printing work station has the highest musculoskeletal risk, while the lowest risk is on the arsenic squeeze work station.